Protection of Children's Rights During Homicide Investigations at Padang Panjang Police Resort, Indonesia - Fitri Yanti; Yenny Fitri Z. (Hakamain: Journal of Sharia and Law Studies, 2026)
This study was motivated by the practice of investigating child homicide offenders at the Women and Children Protection Unit (PPA Unit) of Padang Panjang Police Resort, where investigations were conducted by general investigators rather than specialized child investigators. This condition raises concerns regarding the conformity of investigative practices with child rights protection principles as regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law Number 35 of 2014 concerning Child Protection. Therefore, this study aims to analyze the investigation process involving child homicide offenders and examine whether children’s rights have been substantively fulfilled during such investigations. This study employed an empirical juridical method with a descriptive-analytical approach. Data were collected through interviews, case document studies, and analyses of relevant statutory regulations. Data validity was ensured through source triangulation and cross-checking procedures using official legal documents, including Notification of Commencement of Investigation (SPDP) and case completion reports (P21). The findings indicate that, formally, the rights of children during the investigation process had generally been fulfilled in accordance with existing legal provisions. Children received legal assistance, parental accompaniment, and procedural safeguards during investigations. However, substantively, potential gaps remain, particularly concerning the competence of general investigators in handling child-related cases and the implementation of the best interests of the child principle. The novelty of this research lies in its analysis of the tension between handling serious criminal offenses and implementing child protection principles during investigation practices within the juvenile criminal justice system in Indonesia.